Lack of liberal education at tertiary level: A study on Newman’s The Idea of a University and Hirani’s 3 Idiots - Alam, Md Morshedul; Akter, Golshan Ara; Afrin, Nahida (IIUC Studies, 2021)
This paper deals with the process of university education system, how students will enrich the knowledge and skills, develop the power of reasoning and judgments and promote the creativity. It also advocates a holistic approach in liberal education system that preserves a harmonious relationship among the real cultivation of mind, intellectual excellence and freedom of thought. Newman’s The Idea of a University and Hirani’s3 Idiots have been studied in line with liberal education of university which gives the enlargement of knowledge that pertains to the universal appeal of education system. In this study, some barriers, such as, market value, guardian’s choice and mental depression are addressed as the potential threats for liberal education. Therefore, this research is an attempt to make a comparative study of Newman’s The Idea of a University and Hirani’s3 Idiots as illustrating the liberal education of university and generating an image of liberal education in present society. IIUC Studies Vol.17, December 2020: 43-54